Driven superconducting vortex dynamics in systems with twofold anisotropy in the presence of pinning. (1st July 2022) - Roe, E J; Eskildsen, M R; Reichhardt, C; Reichhardt, C J O
Abstract: We examine the dynamics of superconducting vortices with twofold anisotropic interaction potentials driven over random pinning, and compare the behavior under drives applied along the hard and the soft anisotropy directions. As the driving force increases, the number of topological defects reaches a maximum near the depinning threshold, and then decreases as the vortices form one-dimensional (1D) chains. This coincides with a transition from a pinned nematic to a moving smectic aligned with the soft anisotropy direction. The system is generally more ordered when the drive is applied along the soft direction of the anisotropy. For driving along the hard direction, there is a critical value of the twofold anisotropy above which the system remains aligned with the soft direction. Hysteretic behavior appears upon cycling the driving force, with 1D vortex chains persisting during the decreasing leg below the threshold for chain formation for increasing drive. More anisotropic systems have a greater amount of structural disorder in the moving state. For lower anisotropy, the system forms a moving smectic-A state, while at higher anisotropy, a moving nematic state appears instead.